2013
DOI: 10.1002/gbc.20062
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of atmospheric nutrient inputs to the Atlantic Ocean from 50°N to 50°S based on large‐scale field sampling: Iron and other dust‐associated elements

Abstract: [1] Atmospheric inputs of mineral dust supply iron and other trace metals to the remote ocean and can influence the marine carbon cycle due to iron's role as a potentially limiting micronutrient. Dust generation, transport, and deposition are highly heterogeneous, and there are very few remote marine locations where dust concentrations and chemistry (e.g., iron solubility) are routinely monitored. Here we use aerosol and rainwater samples collected during 10 large-scale research cruises to estimate the atmosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
117
6
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 67 publications
(121 reference statements)
20
117
6
1
Order By: Relevance
“…In contrast to N, dry deposition of s-Fe during M91 was 1-2 (for sample TM09) orders of magnitude higher than reported for the remote South Atlantic (2-7 nmol m −2 d −1 ; Baker et al, 2013). Our average estimate of F d s-Fe during M91 (45 nmol m −2 d −1 , equivalent to ∼ 0.9 mg m −2 yr −1 ) appears to be somewhat higher than the total deposition flux of s-Fe (0.3 mg m −2 yr −1 ) estimated for the region by Krishnamurthy et al (2009;as reported by Messie and Chavez, 2015).…”
Section: Biogeosciencescontrasting
confidence: 53%
“…In contrast to N, dry deposition of s-Fe during M91 was 1-2 (for sample TM09) orders of magnitude higher than reported for the remote South Atlantic (2-7 nmol m −2 d −1 ; Baker et al, 2013). Our average estimate of F d s-Fe during M91 (45 nmol m −2 d −1 , equivalent to ∼ 0.9 mg m −2 yr −1 ) appears to be somewhat higher than the total deposition flux of s-Fe (0.3 mg m −2 yr −1 ) estimated for the region by Krishnamurthy et al (2009;as reported by Messie and Chavez, 2015).…”
Section: Biogeosciencescontrasting
confidence: 53%
“…A local peak in chl:C phyto was also present just north of the equator at ~15° N in the ITCZ. Nutrient inputs into the ITCZ include upwelling (Robinson et al 2006) and nitrogen and ironrich dust blowing off the African continent, which peak in concentration in this region (Baker et al 2013). Samples from the ITCZ create a cluster of points (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…9) caused by P concentrations that ranged between 0.17 and 0.28 µmol kg −1 and exceeded N concentrations, resulting in surface water N* deficits. The very low N concentrations further suggest that atmospheric deposition that is assumed to be another significant N source to the ocean (Duce et al, 2008;Baker et al, 2013) is negligible. However, Sohm et al (2011) observed N 2 fixation within the ABFZ (∼ 13-15 • S) coinciding with decreased thermocline δ 15 N − NO 3 values and elevated dissolved Fe and cobalt surface concentrations (Noble et al, 2012), which are important micronutrients for marine diazotrophic cyanobacteria (Saito et al, 2002(Saito et al, , 2004.…”
Section: Spatial and Temporal Variabilitymentioning
confidence: 98%